Heterogeneous effects of minimum wage on labor market outcomes: A case study from Turkey - Enes Işık; Özgür Orhangazi; Hasan Tekgüç (IZA Journal of Labor Policy, 2020)
We assess the effects of a sharp minimum wage increase on wages, informality, and employment in Turkey, a large developing economy with one of the highest minimum wage-to-average wage ratios among OECD countries and widespread discrepancies between labor market outcomes of women and of men. We look at the quasi-experimental 2016 minimum wage increase and pay attention to identifying information coming from demographic groups. We find that the increase in the minimum wage had an economically substantial and statistically significant positive impact on wages. Despite the positive wage effects of the increase, we find no negative employment effects. However, we show that the minimum wage increase may have caused an increase in the share of informal employment among workers with less than tertiary education, especially for such workers working for small firms.
Keywords: J08; J21; J23; 330; minimum wage; employment; informality; incremental difference-in-differences